Anti-leishmanial activity of Ni(ii), Pd(ii) and Pt(ii) β-oxodithioester complexes1. (27th August 2015) - Yadav, Manoj Kumar; Rajput, Gunjan; Srivastava, Khushboo; Singh, Rakesh K.; Mishra, Rajnikant; Drew, Michael G. B.; Singh, Nanhai
<x xml:space="preserve">Abstract</x> Twelve new β-oxodithioester complexes (1–12) of the type [M(L)2] (M = Ni, Pd, Pt) have been synthesized and fully characterized. 7 and 9 showed impressive anti-leishmanial activity.